Judicial Analysis of Decision Number 590/Pdt.G/2023/PN Bdg on The Legal Status of Business Unit Managers Amid a Legal Vacuum in Foundation Organs - Muhammad Reza Syariffudin Zaki; Axel Christian Putra (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The absence of explicit regulatory mechanisms governing transitional governance in foundations experiencing total vacancy of organs (vacuum of management) has created legal uncertainty, particularly concerning the authority of business unit managers operating under foundations. This normative gap becomes increasingly problematic when foundations manage high-value social assets, raising questions about the limits of managerial authority and the legality of actions undertaken without formally legitimate governing organs. This study addresses two main research questions: (1) how Decision Number 590/Pdt.G/2023/PN Bdg is assessed from the perspective of the Indonesian Foundation Law (Law No. 16 of 2001 as amended by Law No. 28 of 2004); and (2) how judicial law-finding (rechtsvinding) was conducted to resolve the vacancy of foundation organs and its implications for the legal standing of business unit managers. Employing normative juridical research, this study applies statute, case, and conceptual approaches, supported by qualitative analysis of primary and secondary legal materials as well as contextual interviews. The findings demonstrate that the court adopted a dynamic positivism approach, affirming formal ministerial ratification as the decisive criterion of legal legitimacy while simultaneously applying corporate organ theory to clarify the separation of authority between foundation organs and business unit management. The decision confirms that operational continuity does not confer representative authority and that legal legitimacy must remain grounded in formal structure. Academically, this research contributes to the reconstruction of normative boundaries between foundation organs and business unit managers in situations of organs vacancy, highlighting the need for clearer transitional regulatory mechanisms to strengthen legal certainty and protect the social function of nonprofit foundations.